Galápagos sea lion reference genomes - Shafer, Aaron B. A.; Peart, Claire R.; Tusso, Sergio; Maayan, Inbar; Brelsford, Alan; Wheat, Christopher W.; Wolf, Jochen B. W. (Dryad Digital Repository, 2016)
Reference genomes of the Galápagos sea lion in fasta format. One is derived from the CLC workbench and the other from mapping to the Antarctic fur seal.